Comparison of the Claim Ratio Method and the Bornhuetter-Ferguson Chain Ladder Method in Claim Reserve Calculation - Nicea Roona Paranoan; Feby Seru; Ayub Sahala Gultom (Statistika, 2025)
Abstract. Uncertainty in life brings risks that can threaten financial stability, making the existence of insurance crucial for managing such risks. One of the key elements in insurance is the management of claim reserves, which are funds allocated to meet outstanding claim obligations. This study aims to analyze and compare two claim reserve estimation methods, namely the Claim Ratio Method and the Bornhuetter-Ferguson Method, to assess the accuracy of each. The analysis is conducted by calculating claim reserve estimates using both methods based on historical claim data. The data used in this study are simulated data obtained through random sampling using Microsoft Excel. The results show that the Claim Ratio Method produced an estimate of 204,691,130, while the Bornhuetter-Ferguson Method yielded an estimate of 211,097,953. Compared to the Claim Ratio Method, the Bornhuetter-Ferguson Method provides results that are closer to reality, as it takes into account the claim development pattern in more detail, particularly for data with high variability. The study concludes that the choice of estimation method has significant implications for the financial stability of insurance companies. More accurate reserve calculations not only strengthen the solvency and operational efficiency of insurers but also reinforce policyholder trust and confidence in insurance protection. Consequently, the adoption of more robust methods such as the Bornhuetter-Ferguson is recommended, while future research is encouraged to explore alternative or hybrid models that may further improve estimation accuracy in diverse contexts.